Aset global biodynamic leading edge / E.Tavasuria Elangovan - Elangovan, E. Tavasuria (Corporate Communication Unit, Universiti Teknologi MARA, Perak Branch, 2020)
On August 12, 2019, Faculty of Applied Science, University Teknologi MARA, Perak Branch had organised a four-day programme called ‘ASeT Global Biodynamic Leading Edge’ at School of Life Sciences and Technology, Bandung Institute of Technology (ITB), Indonesia. 10 Students from ASeT (Applied Sciences Tapah) Association, UiTM Perak Branch, Tapah Campus were involved in this programme.